The Eco-Friendly Technical Treatment Procedure of Garbage in The Garbage Dump in Semarang City - Darmawan, Edy; Sardjuri, Harsisto; Samsinar Enis, Adhisti (International Journal of Engineering and Technology, 2019)
Of the total of garbage produced, not all garbage carried to landfill and left piled up in temporary disposal site (TPS). Garbage transport from temporary disposal site to the landfill affect the transportation routes because they increase traffic congestion. Not deficient garbage processor in landfill causing a heap the dump solid and mounting. If its left, so that this will disrupt the environment quality of the Semarang City, especially considering the condition of the final disposal site (TPA) Jatibarang who had been discharged the use time. This study aims to to handle the waste problem that is there Semarang, so as to diminish the garbage thrown by to the final disposal site (TPA)  Jatibarang. Research methodology used is the method the qualitative study, because can explain problem in detailed so that it can be known handling exactly. Data is collected through direct observation in the field, interview, and documentation. The results is need to the landfill in every sub-district of Semarang with system burning high temperatures. Our team’s invention of standing furnace incenerator is proven as an effective and efficient garbage dissolving and recycling system. This incenerator is an environmentally friendly technology because it is equipped with major component control pollutants, in order to reduce air pollution caused by exhaust gas. Thus, garbage problems within of the Semarang City can be reduced.